Minimal Clinically Important Difference for Quadriceps Muscle Strength in People with COPD Following Pulmonary Rehabilitation - Oliveira, Ana (2021)
Quadriceps strength training is a key component of pulmonary rehabilitation (PR). Clinical interpretability of changes in muscle strength following PR is however limited due to the lack of cut-off values to define clinical improvement. This study estimated the minimal clinically important difference (MCID) for the isotonic and isometric quadriceps muscle strength assessed with the one-repetition maximum (1RM) and hand-held dynamometry (HHD) in people with chronic obstructive pulmonary disease (COPD) following PR. A secondary analysis of a real life non-randomised controlled study was conducted in people with COPD enrolled in a 12-week community-based PR programme. Anchor and distribution-based methods were used to compute the MCIDs. The anchors explored were the St. George's respiratory questionnaire (SGRQ) and the six-minute walk test (6MWT) using Pearson's correlations. Pooled MCIDs were computed using the arithmetic weighted mean (2/3 anchor, 1/3 distribution-based methods) and reported as absolute and/or percentage of change values. Eighty-nine people with COPD (84% male, 69.9 ± 7.9 years, FEV1 49.9 ± 18.9% predicted) were included. No correlations were found between changes in 1RM and the SGRQ neither between changes in HHD and the SGRQ and 6MWT (p > 0.05). Thus, anchor-based methods were used only in the MCID of the 1RM with the 6MWT as the anchor. The pooled MCIDs were 5.7Kg and 26.9% of change for the isotonic quadriceps muscle strength with 1RM and 5.2KgF for isometric quadriceps muscle strength assessed with HHD. The MCIDs found are estimates to improve interpretability of community-based PR effects on quadriceps muscle strength and may contribute to guide interventions.